FUN CLASSROOM GAMES THAT ACTUALLY HELP KIDS TO LEARN VOCABULARY (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article will outline cost-effective fun classroom games to remember vocabulary perfectly and practise them easily. Also, we will examine several classroom-tested games in order to turn vocabulary into a fun activity. These practical games help kids who are learning English as a second language to learn vocabulary with enjoyment. Additionally, we will discuss Why is vocabulary important? And Why should we use games to teach vocabulary?